Synthesis, Characterization, Electrochemistry, and Spectroscopic Properties of Some Anthracenyl Functionalized Phthalocyanine Complexes of Ruthenium(II). (7th April 2014) - Adeloye, Adewale O.; Ajibade, Peter A.
Abstract : The synthesis of single- and double-decked anthracenyl functionalized ruthenium(II) phthalocyanine complexes has been achieved through a controlled electrophilic aromatic substitution reaction of the free unsubstituted ruthenium(II) phthalocyanine with preformed 9-bromo-10-(2, 3-dimethylacrylic acid)-anthracene and/or 9-bromo-10-(2, 3-dimethylacrylic acid)-dianthracene using 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) as catalyst. The complexes were characterized by IR, UV-Vis, fluorescence, 1 H, 13 C NMR, and elemental analyses. A dimeric complex (C 3 R ′ ′ R u P c, whereR ′ ′ is 9-dianthracenyl-10-(2, 3-dimethylacrylic acid), obtained as the major product of the dianthracenyl-substituted ruthenium phthalocyanine complex displays a strong near-infrared visible absorption band wavelength maxima at 1027 nm (ε = 5.47 × 10 3  M −1  cm −1 ), with an interesting photoluminescent and electroredox active properties.